Konkurencja i jej wpływ na działania inwestycyjne przedsiębiorstw - Parvi, Rafał (Competition and Its Influence Upon Enterprises Investment Operations, 2006)
The first firm (textile-clothing production) has showed a growth trend to generate bigger net profit and revenues, having taken a bank credit. At the same time, the firm has bought some machines to produce goods from non-weave materials and could run current economic activity without any threats of destabilization of financial availability. So, it is the example of well-developing and investing company, which came up to the requirements of economic competition.The second firm (processing of secondary raw materials), which has been running aggressive and expansive policy as a leader on a specific market, after taking a bank credit is still the leader and has good financial availability. Thanks to this credit, it has gained the new ready markets and extended its operations on the Polish market from 49% to 78%. The firm has made investments on the existing processing lines, has developed the net of gaining cullet, has assembled the special industrial waste utilization line and employed highly professional stuff. The firm has been able to come up to the market demands and competition thanks to its expansive and also risky economic activity.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 200-205